Citizen centric assessment framework for e-governance services quality. (2018) - Singh, Vinay; Singh, Garima
Citizen-centric e-governance services are essential to enhance the quality of life of citizens while ensuring citizen empowerment. The present study proposes a framework of assessing quality of e-governance services from the citizens' perspective to find out the degree of its quality impacting citizen satisfaction. The framework is validated through primary data collected from 213 respondents. Confirmatory factor analysis and structured equation modelling are employed to validate the model. The results depict quality of e-governance service and the information being disseminated to the citizens' impact on their satisfaction significantly. The study contributes a parsimonious model that can significantly contribute in future theoretical advances in e-governance quality assessment. The findings can bridge the gap between government initiatives and citizens' needs. Thus, designing high quality e-governance services while keeping the needs and expectations of citizen in focus translates its functional efficacy.